Salvage of Herniated Flow Diverters Using Stent and Balloon Anchoring Techniques: A Technical Note - Jagadeesan, Bharathi D. (Interv Neurol, 2017)
BACKGROUND: The pipeline embolization device (PED; Medtronic, MN, USA) can sometimes herniate into the aneurysmal sac in an unexpected manner during or shortly after its deployment due to device foreshortening. In this report, we describe 2 endovascular techniques, which can be used to reposition a herniated PED construct into a more favorable alignment. SUMMARY: In a 67-year-old patient who had an intraprocedural herniation of a PED device into a giant cavernous aneurysm, a stent anchor technique was used to reverse the herniation, reorient the PED construct, and achieve successful flow diversion. In a different patient with a giant superior hypophyseal aneurysm, a balloon anchor technique followed by deployment of an LVIS Jr (Microvention, Tustin, CA, USA) stent was used to reverse the herniation into the aneurysmal sac. KEY MESSAGES: Stent anchor and balloon anchor techniques as described here can be used to reposition PED constructs, which have unexpectedly herniated into the aneurysm sac during attempted flow diversion for the treatment of giant aneurysms.